Cesarean Scar Ectopic Pregnancy in Second Trimester A Case Report - Yasmin, Fowzia; Jahan, Muna Shalima; Alam, Irin Parveen; Rahman, Md Towhidur; Akhter, Parul; Nahid, Sanjida (Sir Salimullah Medical College Journal, 2022)
Cesarean scar ectopic pregnancy (CSEP) is one of the rarest form of ectopic pregnancy. It is characterized by a gestation implanted in a caesarean section scar and surrounded by the myometrium and the fibrous tissue of the scar. With rising cesarean delivery rates and widespread use of ultrasound in early pregnancy, there is a parallel upward trend in the incidence of CSEP. The most significant risk associated with a CSEP is an early uterine rupture with life threatening maternal hemorrhage leading to hysterectomy and loss of reproductive potential. An early diagnosis can offer conservative treatment options capable of preserving the uterus. Here we present a case 25-year-old G-3, P2(both LSCS - lower segment cesarean section), admitted at her 17 weeks of pregnancy with per vaginal spotting and diagnosed as a case of missed abortion. All her vitals were normal. Three days after her admission she was diagnosed with cesarean scar ectopic pregnancy and managed by laparotomy followed by total abdominal hysterectomy. Sir Salimullah Med Coll J 2021; 29(2): 172-175